Spatially resolved single-cell atlas reveals the macroevolutionary trajectory of animal hearts - Shanshan Lian; Wei Wang; Yaoxin Liu; Meina Lu; Wentao Han; Jiaxin Luo; Xuejiao Zhang; Yue Pang; Yuru Li; Yufeng Li; Xin Dang; Peiyan Wang; et al. (Science, 2026)
Animal hearts display diverse anatomical structures during adaptive evolution. Here, we present a multi-omics atlas of adult hearts from 27 species across chordates, arthropods, and mollusks. Joint analysis indicates that Bilateria hearts share a core gene repertoire, taking a stepwise “add-on” approach as a universal evolutionary strategy. The proto-heart is populated by key cell types, including cardiomyocytes, fibroblasts, endothelial, and neural cells, which maintained core signatures while evolving with shifts in living environments and corresponding adaptations in the cardiovascular system. Additionally, we reveal an evolutionarily conserved cardiomyocyte state dynamic potentially linked to cardiac development and stress responses. Finally, we identify a common molecular program underpinning chamber evolution from a ventricular foundation. Together, this work establishes a resource for understanding the intrinsic mechanisms of heart evolution.